2011
DOI: 10.2165/11536960-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Child Health Utility 9D Health States with a Young Adolescent Sample

Abstract: QALYs are increasingly being utilized as a health outcome measure to calculate the benefits of new treatments and interventions within cost-utility analyses for economic evaluation. Cost-utility analyses of adolescent-specific treatment programmes are scant in comparison with those reported upon for adults and tend to incorporate the views of clinicians or adults as the main source of preferences. However, it is not clear that the views of adults are in accordance with those of adolescents on this issue. Hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(53 citation statements)
references
References 28 publications
0
53
0
Order By: Relevance
“…Since these estimates were on an interval scale, re-scaling via an external cardinal valuation task using traditional health state valuation methods, e.g., the TTO or SG, was necessary to ensure that 0 represented the death state. Whilst it would be ideal to conduct the re-scaling using data generated from an adolescent sample, our previous research has highlighted the ethical difficulties associated with this process (Ratcliffe et al, 2011). In addition we found a poor level of understanding of TTO and SG methods in general in adolescents (Ratcliffe et al, 2011).…”
Section: Adolescent Scoringmentioning
confidence: 83%
See 2 more Smart Citations
“…Since these estimates were on an interval scale, re-scaling via an external cardinal valuation task using traditional health state valuation methods, e.g., the TTO or SG, was necessary to ensure that 0 represented the death state. Whilst it would be ideal to conduct the re-scaling using data generated from an adolescent sample, our previous research has highlighted the ethical difficulties associated with this process (Ratcliffe et al, 2011). In addition we found a poor level of understanding of TTO and SG methods in general in adolescents (Ratcliffe et al, 2011).…”
Section: Adolescent Scoringmentioning
confidence: 83%
“…Whilst it would be ideal to conduct the re-scaling using data generated from an adolescent sample, our previous research has highlighted the ethical difficulties associated with this process (Ratcliffe et al, 2011). In addition we found a poor level of understanding of TTO and SG methods in general in adolescents (Ratcliffe et al, 2011). Hence, for the purposes of this study we utilised the mean health state values derived from a conventional TTO task for a selection of CHU9D health states from a sample of young adults (aged 18 to 29 years) to re-scale the ordinal values derived from the BWS DCE task onto the 0 = death to 1 = full health QALY scale (Ratcliffe et al, 2015a).…”
Section: Adolescent Scoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Research comparing DCE and TTO has found that both techniques have equivalent levels of respondent comprehension and completion. 62 However, this study did not test the DCE TTO method, which may be more difficult than standard DCE owing to the addition of an attribute for duration.…”
Section: Influences On Responses To Health-state Valuation Tasksmentioning
confidence: 94%
“…However, earlier work comparing DCE and TTO found that both techniques could be understood equally well and had high completion rates. 62 On the other hand, the very factor that makes iterative tasks easier may introduce bias of its own. There is a literature on contingent valuation and willingness to pay in health economics, where it has been shown that iterative tasks may be susceptible to biases because respondents do not interpret the series of binary choices as independent.…”
Section: Binary Choice Methodsmentioning
confidence: 99%